Optimization of the biodecolorization activity of the Ayapers dye removal by Halmonas sp. isolated from Urmia Lake - Mohammad Ansarizadeh; Tayebeh Tahamtan; Mostafa Leili; Masoud Yousefi; Ehsan Gharehchahi; Mohsen Kalantari (Shiraz University of Medical Sciences, 2020)
Background: Among chemical dyes, Azo dyes, as environmental synthetic pollutants, are most commonly used in a bunch of different colors in different industries, especially in textile industry to a large extent. Methods: Due to some limitation and difficulties to remove these pollutants from the environment, the biological filtering method, as the economically and optimal methods, are preferred. Using the Taguchi method and evaluation of such factors in the environment as temperature pH, color density and concentration of salt, we studied the optimal condition of Halomunas PTCC1132 bacteria decolorization in order to compare it with the Aryapress dye removal from aquatic environment. Therefore, 16 experiments were designed according to Array Table in 4 factors and 4 levels. The results were then analyzed using a computer the program named Qualitek-4. Results: The results showed that this salt, loving bacterium Halomonas strain PTCC1714, has the ability of bleaching in a wide range of salts till 20%, pH (5-9) and dye tolerance up to 5 gr/lit (500 ppm), and has the highest rate of decolorization in 100 ppm. Conclusions: According to the  results with an  optimal growth condition- the temperature of 40c, pH of 7.5, and the salt concentration of 10% up to 93% - the strain was capable of removing the Azo dye Aryapress color with the concentration of 100 ppm which is a considerable amount and can be used in biological treatment of industrial textile sewage.